Levels of C-Reactive Protein and Sodium May Differentiate a Perforated Appendix from a Nonperforated Appendix in Children. (16th June 2021) - Nissen, M.; Tröbs, R.-B.
Abstract : Background . Acute appendicitis (AA) might be amenable to conservative antibiotic treatment, whereas a perforated appendix (PA) necessitates surgery. We investigated the value of clinical–laboratory markers in distinguishing AA from a PA. Methods . Retrospectively obtained preoperative parameters for 306 consecutive patients (<18 years) with histologically confirmed appendicitis (AA (n = 237 ) vs . PA (n = 69 )), treated at our institution between January 2014 and December 2017. Results . A PA was associated with male preponderance, younger age, decreased sodium level and increased white blood cell count, Tzanakis score, C-reactive protein (CRP) level, and CRP-to-lymphocyte ratio (CLR). Upon discrimination analysis, CLR and CRP displayed the highest accuracy in differentiating a PA from AA. Regression analysis identified levels of CRP, sodium, and the Tzanakis score as independent predictors for a PA. Conclusion . Levels of CLR, CRP, sodium, and Tzanakis score might support decision-making regarding treatment options for pediatric appendicitis.